Handbook of transport strategy, policy and institutions - Hensher, David A., 1947-; Button, Kenneth, 1948- (Emerald, 2005)
Privatisation, regulation, deregulation, competition, funding, evaluation: these are all transport policy issues of great current interest worldwide, in the public arena as well as among researchers. In 46 chapters by acknowledged experts on their topics, these and other aspects of transport policy and planning are addressed in this, the sixth "Handbook in Transport". The work is organised into sections covering: Institutional Settings and Markets; Planning Perspectives; Asset Management and Funding; Regulatory Issues; Evaluation Frameworks; and National Studies.Within this section structure this wide-ranging volume embraces: the collection of data (and its transformation into information); the formation of policy objectives by government (at all its different levels); the establishment of institutional structures to attain these goals; the resourcing of these institutions; the implementation of actions; and the policing and monitoring of outcomes. It employs a variety of disciplinary perspectives, including economics, politics, law, physical planning, psychology and engineering.It will be of value to students, researchers, and practitioners approaching transport from any of these perspectives.
Includes indexes.
Keywords: Transportation -- General.; Business & Economics -- Industries -- Transportation.; Transport industries.; Transport planning & policy.; Transportation and state.; elektronické knihy; electronic books